Meis1: effects on motor phenotypes and the sensorimotor system in mice - Aaro V. Salminen; Lillian Garrett; Barbara Schormair; Jan Rozman; Florian Giesert; Kristina M. Niedermeier; Lore Becker; Birgit Rathkolb; Ildikó Rácz; German Mouse Clinic Consortium; Martin Klingenspor; Thomas Klopstock; et al. (The Company of Biologists, 2017)
MEIS1 encodes a developmental transcription factor and has been linked to restless legs syndrome (RLS) in genome-wide association studies. RLS is a movement disorder leading to severe sleep reduction and has a substantial impact on the quality of life of patients. In genome-wide association studies, MEIS1 has consistently been the gene with the highest effect size and functional studies suggest a disease-relevant downregulation. Therefore, haploinsufficiency of Meis1 could be the system with the most potential for modeling RLS in animals. We used heterozygous Meis1-knockout mice to study the effects of Meis1 haploinsufficiency on mouse behavioral and neurological phenotypes, and to relate the findings to human RLS. We exposed the Meis1-deficient mice to assays of motor, sensorimotor and cognitive ability, and assessed the effect of a dopaminergic receptor 2/3 agonist commonly used in the treatment of RLS. The mutant mice showed a pattern of circadian hyperactivity, which is compatible with human RLS. Moreover, we discovered a replicable prepulse inhibition (PPI) deficit in the Meis1-deficient animals. In addition, these mice were hyposensitive to the PPI-reducing effect of the dopaminergic receptor agonist, highlighting a role of Meis1 in the dopaminergic system. Other reported phenotypes include enhanced social recognition at an older age that was not related to alterations in adult olfactory bulb neurogenesis previously shown to be implicated in this behavior. In conclusion, the Meis1-deficient mice fulfill some of the hallmarks of an RLS animal model, and revealed the role of Meis1 in sensorimotor gating and in the dopaminergic systems modulating it.